Enforcement Of Law Against Criminal Acts Related To Trademarks By The Special Criminal Investigation Directorate Of The Bali Provincial Police - Putra, I Putu Diarsa; Sihotang, Erikson; Suryana, Kadek Dedy (Pelopor Publikasi Akademika, 2025)
Enforcement of trademark-related criminal offenses by the Special Criminal Investigation Directorate of the Bali Provincial Police, in accordance with Law No. 20 of 2016 on Trademarks and Geographical Indications, is carried out through preventive law enforcement measures, which prioritize persuasive approaches and public awareness campaigns to prevent potential trademark infringements, as well as enhancing the knowledge of trademark owners through outreach activities. Preventive enforcement involves appeals and approaches, including socialization activities for registered trademark owners, and repressive measures, which include strict law enforcement, including the arrest and investigation of perpetrators, as well as the seizure of counterfeit trademark evidence. The obstacles faced by investigators from the Special Criminal Investigation Directorate of the Bali Regional Police in enforcing trademark rights include, first, legal obstacles, as trademark rights are a complaint-based offense, and second, obstacles related to law enforcement, namely the limited vocational training for personnel in Sub-Directorate I of the Special Criminal Investigation Directorate of the Bali Regional Police. Third, societal factors include the lack of public participation in providing information regarding suspected trademark infringement crimes.